MEMBANGUN KETERLIBATAN SISWA DISEKOLAH SEBAGAI BAGIAN DARI MAKHLUK SOSIAL - Yahya Mof; Muhammad Fahmi Nurani (Nizham Journal of Islamic Studies, 2022)
Students show negative behavior in class because they are not involved in the lessons that the teacher presents. This may happen because the material presented is not at the academic level for students. Lack of involvement can occur because students do not actively participate in class activities. teachers and administrators have the opportunity to observe the classroom and the learning strategies used to engage students. After the class visit, teachers and administrators have the opportunity to discuss strategies that score high and the types of activities that increase the level of involvement. Teachers who can experience and observe what high student engagement looks like by participating in the learning practice inventory guide can be the school's best resource in educating other teachers.